2001
DOI: 10.1037/0021-9010.86.3.481
|View full text |Cite
|
Sign up to set email alerts
|

Toward a theory of individual differences and leadership: Understanding the motivation to lead.

Abstract: A broad, integrative theoretical framework for understanding the relationship between individual differences and various leader behaviors is presented; it proposes a new individual-differences construct called the motivation to lead (MTL). A large-scale study using 3 samples in different occupational and cultural contexts shows 3 factors underlying MTL, namely, affective-identity, noncalculative, and social-normative MTL. A parsimonious model of antecedents to MTL is developed through hierarchical regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

51
1,082
5
28

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 611 publications
(1,166 citation statements)
references
References 29 publications
51
1,082
5
28
Order By: Relevance
“…Helgstrand and Stuhlmacher (1999) found that both Danish and US high school and undergraduate students rated leaders who were feminine and individualistic as most effective (Danes were lower on PD). Finally, using horizontal (H) and vertical (V) aspects of IND and COL (i.e., VCOL represents a tendency to view the self as an aspect of the group, see members of an ingroup as different from the self, and accept inequality; HCOL represents the tendency to view the self as an aspect of the group, see members of an ingroup as similar to the self, and value equality; VIND represents the extent to which an individual's self-concept is autonomous but expects inequality; and HIND represents the extent to which an individual's self-concept is autonomous and the individual is seen as equal to others), Chan and Drasgow (2001) surveyed military recruits and junior college students in Singapore and the US to explore links between cultural values and various dimensions of motivation to lead (MTL). They found that HIND was negatively related to noncalculative MTL (i.e., people lead only when they are not calculative about the costs of leading relative to the benefits) and socialnormative MTL (i.e., people lead because they feel a sense of responsibility or duty); and VIND was positively related to affective identity MTL (i.e., some people just like to lead others) and socialnormative MTL, and negatively related to noncalculative MTL.…”
Section: Leadership (4)mentioning
confidence: 99%
“…Helgstrand and Stuhlmacher (1999) found that both Danish and US high school and undergraduate students rated leaders who were feminine and individualistic as most effective (Danes were lower on PD). Finally, using horizontal (H) and vertical (V) aspects of IND and COL (i.e., VCOL represents a tendency to view the self as an aspect of the group, see members of an ingroup as different from the self, and accept inequality; HCOL represents the tendency to view the self as an aspect of the group, see members of an ingroup as similar to the self, and value equality; VIND represents the extent to which an individual's self-concept is autonomous but expects inequality; and HIND represents the extent to which an individual's self-concept is autonomous and the individual is seen as equal to others), Chan and Drasgow (2001) surveyed military recruits and junior college students in Singapore and the US to explore links between cultural values and various dimensions of motivation to lead (MTL). They found that HIND was negatively related to noncalculative MTL (i.e., people lead only when they are not calculative about the costs of leading relative to the benefits) and socialnormative MTL (i.e., people lead because they feel a sense of responsibility or duty); and VIND was positively related to affective identity MTL (i.e., some people just like to lead others) and socialnormative MTL, and negatively related to noncalculative MTL.…”
Section: Leadership (4)mentioning
confidence: 99%
“…To illustrate with recent examples: Duckitt and Sibley (2009) considered the belief that some groups are superior to others as " deriving directly from the personality dimension of Tough versus Tendermindedness (in Big-Five terms, low Agreeableness)" (p. 102); Chan and Drasgow (2001) argued that Big Five traits "relate to leader behaviors through the individual's motivation to lead, which in turn affects the individual's participation in leadership roles " (p. 481; also Judge, Piccolo, & Kosalka, 2009). Most directly, Terracciano and McCrae (2012) argued that "it is perfectly reasonable to say that party going is caused (proximally) by liking people and that it is caused (distally) by extraversion" (p. 449; italics added in examples above).…”
Section: Locating Structural Factors In the Personality Systemmentioning
confidence: 99%
“…Motivacija zaposlenih se ostvaruje u svakodnevnom ponašanju i zajedničkom radu lidera i zaposlenih. Ljudi su nosioci ideja, kreativnosti, produktivnosti i kva liteta, a da bi ispoljili i aktivirali svoj potencijal potrebna je organizaciona sredina u kojoj se za posleni tretiraju kao saradnici i partneri (Beck, 2000;Chan & Drasgow, 2001;Kouzes & Posner, 2002;Petri & Govern, 2004;Burke, Lake & Paine, 2009;Yukl, 2010).…”
Section: Motivacija I Liderstvounclassified